Survey of knowledge on calcium carbide use in fruit ripening and associated health risks among fruit sellers and consumers in Ado-Ekiti Nigeria - Orok, Edidiong; Okeke, Uchenna; Williams, Tonfamoworio; Adeniyi, Funmilayo; Ikpe, Favour; Femi-Oyewo, Mbang (Discover public health, 2024)
Background This study aimed to assess the methods used for ripening fruits by sellers and to examine the knowledge regarding the health risks associated with the use of calcium carbide (CaC 2 ) among both fruit sellers and consumers in Ado-Ekiti. Methods The study employed a cross-sectional design, utilizing a semi-structured questionnaire administered in major markets within Ado-Ekiti. Knowledge levels were categorized into good (> 70% score), fair (50–69% score), and poor (< 50% score). One way Analysis of variance (ANOVA) and Independent sample t-test was used to indicate knowledge score difference with respect to socio demographic characteristics. Results The study involved 357 consumers and 20 fruit sellers, with a majority being females (54.9% of consumers; 80.0% of sellers) and aged predominantly between 18–27 years and 28–39 years. The findings revealed that the use of CaC 2 (50%) and natural ripening methods (100%) were common among fruit sellers. Sellers cited cancer (60%), bacterial infections (35%), and chest tightness (15%) as associated risks with CaC 2 usage. Similarly, consumers expressed concerns about consuming CaC 2 -ripened fruits, attributing risks such as abdominal burns (70%), cancer (70.6%), and diarrhoea (67.3%). A significant proportion of sellers (90%) exhibited poor knowledge regarding the risks associated with CaC 2 , while 24.6% of consumers demonstrated fair knowledge on the subject. Conclusion The study identified common fruit ripening practices among sellers. Fruit sellers showed poor knowledge, while consumers displayed fair to poor understanding of health risks linked to calcium carbide use in artificial fruit ripening.